The Idea of Building A House of Maqashid Sharia Perspective - Jefry Tarantang; Ahmadi Hasan; Ibnu Elmi A. S. Pelu; Ahmad Dakhoir (Journal of Islamic Architecture, 2023)
This study discusses the construction of residential houses in accordance with sharia principles, both in the art and science of designing and constructing buildings and residential houses, which is then called architectural fiqh. Residential construction in addition to paying attention to architecture must also pay attention to aspects of Islamic law. Attention of classical and contemporary scholars very few specifically talk about architecture from the point of view of jurisprudence. So far, studies on architecture have mostly studied Islamic architecture, but no one has studied architecture in a fiqh approach. So, through the fiqh approach, a new study was initiated, namely architectural fiqh. This research is a literature study with a focus on fiqh studies in building sharia residential houses using a conceptual approach and an architectural fiqh approach which is analyzed through qualitative content analysis. The findings of this study indicate that the construction of residential houses so far only pays attention to architectural aspects, so there is a need for a fiqh and architectural approach (architectural fiqh), namely building houses according to sharia signs such as aspects of worship, muamalah, neighborly etiquette and ‘urf or adat. That occurs in society. Through the architectural fiqh approach, it directs to build and maintain sharia residential homes in accordance with sharia maqashid, namely maintaining religion, soul, mind, lineage, and property.